Technical Guidance on Silage Making as Cattle Feed in Lawoila Village, Konda Sub-District, South Konawe - Badaruddin, Rusli; Saili, Takdir; Syamsuddin, Syamsuddin; A Hadini, Hairil; Aka, Rahim; Lestari, Yuni; Zulkarnain, Deki; Munadi, La Ode Muh. (Asian Journal of Community Services, 2024)
This abstract presents the results of community service activities conducted by the Faculty of Animal Husbandry lecturers and postgraduate lecturers in Lawoila Village, Konda Sub-District, South Konawe Regency. The main focus of this activity is to provide technical guidance in silage making with the aim of maximizing the preservation of nutrient content in rice straw, thus enabling it to be stored for a longer period. The methods applied in this community service program include observation, counseling, and evaluation to ensure its effectiveness. The results of this community service activity indicate that the community in Lawoila Village, Konda Sub-District, responded well to silage-making. They demonstrated a high level of enthusiasm in understanding the concept of feed management.